The Influence Of Education Through Video Media On Knowledge Of How To Use Insulin Pen In Diabetes Mellitus Patients At Pesanggrahan Hospital, Selatan Jakarta - Muniasih, Rantri; Dinaryanti, Ratna Sari (Sean Institute, 2023)
Diabetes is a series of chronic metabolic disorders caused by the pancreas not producing enough insulin, causing both absolute and relative insulin deficiency, resulting in increased glucose concentration in the blood. Pharmacological handling of insulin includes administering an insulin pen that is used correctly. This research aims to determine the effect of education through video media on knowledge of how to use insulin pens in diabetes patients. This research method uses a Quasi-Experimental design with a research design of